Evidence for a new paradigm of gonorrhoea transmission: cross-sectional analysis of Neisseria gonorrhoeae infections by anatomical site in both partners in 60 male couples. (17th April 2019) - Cornelisse, Vincent Jasper; Williamson, Deborah; Zhang, Lei; Chen, Marcus Y; Bradshaw, Catriona; Hocking, Jane S; Hoy, Jennifer; Howden, Benjamin P; Chow, Eric P F; Fairley, Christopher K
Abstract : Objective: Gonorrhoea transmission between men is currently thought to occur primarily to and from the urethra. Transmission without urethral involvement, from throat-to-throat and throat-to-anus, is considered to be uncommon. Using gonorrhoea results from male couples, we aimed to investigate the transmission dynamics of gonorrhoea. If current medical consensus is correct, then most throat and anal infections should be explained by the partner's urethral infection. Methods: This is a cross-sectional analysis of gonorrhoea diagnosed by nucleic acid amplification tests in both partners in male couples who attended Melbourne Sexual Health Centre together between March 2015 and June 2017. Isolates obtained from culture-positive infections underwent whole genome sequencing to assess phylogenetic relatedness between partners. Results: In all 60 couples (120 men) at least one partner had gonorrhoea, and isolates had very high phylogenetic relatedness between partners. After excluding men with urethral gonorrhoea, among 32 men with anal gonorrhoea, 34% (95% CI 19% to 53 %) had a partner with throat gonorrhoea. After excluding couples where either man had urethral gonorrhoea, among 48 couples in which at least one man had throat gonorrhoea, in 23% (95% CI 12% to 37 %) of couples both men had throat gonorrhoea. Conclusions: The observed gonorrhoea positivity when urethral infection is absent supports a new paradigm of gonorrhoea transmission, where the throat is a major source of gonorrhoea transmission between men, through tongue kissing, oroanal sex and saliva use as anal lubricant. Public health messages may need to address the risk of saliva exposure during sex.